Distal learning of the incremental capacity curve of a LiFePO4 battery. (2nd November 2020) - Sánchez, Luciano; Otero, José; González, Manuela; Anseán, David; Zülke, Alana A; Couso, Inés
Abstract: An intelligent model of the incremental capacity (IC) curve of an automotive lithium-ferrophosphate battery is presented. The relative heights of the two major peaks of the IC curve can be acquired from high-current discharges, thus enabling the state of health estimation of the battery while the vehicle is being operated and in certain cases, aging mechanisms can be suggested. Our model has been validated using a large dataset (number of batteries) representing different degradation scenarios, obtained from a recently available open-source database.